Web services and formal methods 4th International Workshop, WS-FM 2007, Brisbane, Australia, September 28-29, 2007 : proceedings - WS-FM 2007 (Lecture notes in computer science ;, 2025)
This book constitutes the thoroughly refereed post-workshop proceedings of the 4th International Workshop on Web Services and Formal Methods, WS-FM 2007, held in Brisbane, Australia, in September 2007 in conjunction with the 5th International Conference on Business Process Management, BPM 2007. The 9 revised full papers presented together with 2 invited papers were carefully reviewed and selected from 22 submissions. The papers address the application of formal methods and reasoning techniques to Web service technology, and formal theories inspired by developments in the field of Web services. The papers feature topics such as service-oriented analysis and design, formal approaches to enterprise modeling and business process modeling, model-driven development, testing, and analysis of Web services, Web services for business process management, security, performance and quality of Web services, Web service coordination and transactions, Web service ontologies and semantic description, goal-driven discovery and composition of Web services, complex event processing in service-oriented architectures, as well as semi-structured data management and XML technology. Towards a theory of web service choreographies -- Controlling Petri net process models -- Extending model checking to data-aware temporal properties of web services -- Analyzing BPEL4Chor: verification and participant synthesis -- Scalable formalization of publish/subscribe messaging scheme based on message brokers -- A Feature-complete Petri net semantics for WS-BPEL 2.0 -- From BPEL to SRML: a formal transformational approach -- Modeling web service interactions using the coordination language Reo -- Synthesis of web services orchestrators in a timed setting -- From public views to private views – correctness-by-design for services -- Event structure semantics of Orc.